THE IMPORTANCE OF CONTEMPORARY ISLAMICSTUDIES - Dilnura Choriyeva; Dilshodjon Toshpulatov (TADQIQOTLAR, 2025)
Abstract: This article analyzes the essence, methodology, and scientificsignificanceof contemporary Islamic studies. It explores the role of Islamin social lifebasedonmodern academic approaches and examines the relevance of Islamic studiestoday,as well as its connection with international scholarly research. Thepaperalsohighlights the contribution of modern Islamic studies to cultural, political, andsocial stability.